Mg/Al-CO3 layered double hydroxide nanorings - Yang, M; Liu, J; Chang, Z; Williams, G; O'Hare, D; Zheng, X; Sun, X; Duan, X (2011)
Mg/Al-CO3 Layered Double Hydroxide (LDH) nanorings with a 750 nm exterior diameter and 250 nm interior diameter were synthesized in an organic/water solvent system via a urea hydrolysis method, using Mg 10(OH)18Cl2·5H2O nanowires as precursors. X-Ray diffraction and Fourier-transform infrared spectroscopy clearly revealed the nanorings to comprise Mg/Al-CO3 LDH. The character of the precursor materials and the ratio of organic solvents to water used for reaction played crucial roles in determining the final ring-like morphology. A possible mechanism was proposed for the LDH nanoring formation. The unique LDH nanorings exposed a higher specific surface area and larger pore volume than plate-like and flower-like analogues, and thus were further explored for their catalytic activity using the Knoevenagel reaction between benzaldehyde and diethyl malonate as a probe reaction. The ring-like structure displayed a significantly enhanced catalytic performance above other analogues. This journal is © The Royal Society of Chemistry.